AB1184 BURDEN OF DISEASE AND DIRECT HEALTH CARE COSTS FOR PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS IN WESTERN AUSTRALIA. (2nd June 2020) - Raymond, W.; Ngo, G.; Ognjenovic, M.; Li, I.; Cheah, P.; Chakera, A.; Mclean-Tooke, A.; ". Nossent, J.
Abstract : Background: Systemic Lupus Erythematosus (SLE) is a chronic multiorgan disease with an unpredictable disease course, which requires monitoring for disease activity, treatment efficacy and comorbidity. Data on the healthcare utilization and cost of SLE, especially from Australia are scarce. Objectives: To determine the healthcare utilisation and estimated costs of inpatient admissions (IP), emergency (ED) and outpatient (OPD) hospital visits and investigations for SLE patients in Western Australia (WA). Methods: This is a longitudinal cohort study of SLE patients seen at a metropolitan public hospital, with ≥6 months of follow-up (n=179, 95% female; baseline age 36.2 ± 15.2 years). Electronic medical records provided data on OPD, ED and IP visits, and investigations conducted at public hospitals from January 2000 - December 2019. Direct healthcare costs were estimated from public hospital expenditure aggregates in FY2018/19. Results: During a median observation period of 11.0 years (IQR 7.4, 13.5), SLE patients required 13, 320 OPD visits for a median of 5.3 (IQR 3.0, 9.3) appointments per annum. The majority of OPD visits were with Rheumatology (n=1, 986, 14.9%), Immunology (n=1, 527, 11.5%), and allied health services (n=1, 952, 14.7%), followed by Ophthalmology (n=1, 385, 10.4%), maternal & fetal health (n=873, 6.6%) and Renal medicine (n=844, 6.3%). In total 143 patients (79.9%) attended ED on average of 3 times (IQR 2, 7; ED visit rate 44.0 (95%CI 41.0, 47.0) per 100 person years. Overall, 125 patients (69.8%) were hospitalised at average 3 times (IQR 2, 6), with a mean LOS of 5 days (IQR 3, 12) for an IP rate of 37.6 per 100 patient years (95%CI 34.8, 40.5). Only 12.8% of patients did not attend ED or IP in the public health care system. A total of 367, 067 laboratory investigations were performed (median nr. of tests per patient 205 (±290) per year) across fields of haematology/biochemistry (89%), immunology (5%), microbiology (4.5%) and histopathology (<1%). Minimum estimates for direct health care cost during the study period were 25.4 million AUD (IP 11m, OPD 6.3m, ED 0.9m and investigations 9.1m) for a crude annual cost of 14, 088 AUD per patient. Conclusion: SLE patients have extensive healthcare utilization across a range of outpatient and inpatient services. The main direct costs for this multidisciplinary health care provision are for disease monitoring and in-hospital treatment. Based on these conservative cost estimates to which medication cost need to be added, total costs for SLE care in WA are projected to be significantly higher than reported from Europe. Acknowledgments: The authors wish to acknowledge the support of Arthritis Foundation of WA and Lupus WA Disclosure of Interests: warren raymond: None declared, Georgia Ngo: None declared, Milica Ognjenovic: None declared, Ian Li: None declared, Patrick Cheah: None declared, Aron Chakera: None declared, Andrew McLean-Tooke: None declared, Johannes ("Hans") Nossent Speakers bureau: Janssen